Computational fluid dynamic (CFD) comparison of combustion characteristic between hydrogen and gasoline fuels using openfoam - Muhammad Akaashah Bin Amiruddin (2023)
In this research, a Computational Fluid Dynamics (CFD) study on combustion characteristics of hydrogen and gasoline fuels in ICE is conducted using an open source CFD software which is OpenFOAM in order to analyse the parameters and comparing advantages and disadvantages of both fuels. To complete this paper, the literature review has been made by reviewing 10 documents relating to journal and research paper on hydrogen fuels and gasoline fuel inside ICE in order to find gaps in those papers. Then, geometrical construction of combustion chamber and numerical fuels' parameter are created to conduct CFD simulation. Every results obtain are tabulated and calculated using Otto Cycle combustion system to compared with existing research for validation process. At the end of the research, it can be observed that hydrogen fuel produce lesser torque (N.m) and power distribution (kW) compared to gasoline fuel due to smaller number of temperature (K) and pressure (kPa) produce after ignition process (Power Stroke).